2015
DOI: 10.4172/1948-5956.1000323
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Finger Prints of Brain Cancer Glioblastoma Multiforme from Four Different Patients by Using Near Infrared Raman Spectroscopy

Abstract: To explore the effectiveness of Raman spectra to diagnose brain cancer glioblastoma multiforme (GBM), we investigated the Raman spectra of single cell from four different GBM cell lines developed from four different patients and analyzed the spectra. The Raman spectra of brain cancer (GBM) cells were similar in all these cell lines. The results indicate that Raman spectra can offer the experimental basis for the cancer diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In addition to collagen rearrangement, a switch in the level of the different collagen types, has also been shown to occur during glioma progression [ 29 , 42 44 ]. Overall, our study confirmed that Raman peaks that increase during glioma progression, could be assigned to an increase in collagen, proteins, lipids, haemoglobin, and DNA levels [ 12 , 32 , 45 ]. In addition, there was a decrease in antioxidant carotenoids in grade IV compared to III, a common feature in RS cancer research studies [ 12 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 79%
“…In addition to collagen rearrangement, a switch in the level of the different collagen types, has also been shown to occur during glioma progression [ 29 , 42 44 ]. Overall, our study confirmed that Raman peaks that increase during glioma progression, could be assigned to an increase in collagen, proteins, lipids, haemoglobin, and DNA levels [ 12 , 32 , 45 ]. In addition, there was a decrease in antioxidant carotenoids in grade IV compared to III, a common feature in RS cancer research studies [ 12 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 79%
“…Decreased lipid signals, particularly at 1450 cm −1 were found in glioma U251 cell culture and human GBM [37,100,101]. However, high lipid signals were detected in astrocytoma grade IV, recurrent glioma and after temozolomide treatment [102][103][104]. Uckermann et al also provided similar result where elevated lipid signals were detected by FTIR spectroscopy [105].…”
Section: Lipids Signal Intensities In Gliomamentioning
confidence: 75%
“…The average survival rate from the time of diagnosis is less than twelve months, and even in the least aggressive forms, GBM causes most patients to die within two year time frame 1 , 2 . Numerous studies have focused on gaining a better understanding of different molecular mechanisms exploited by invading GBM tumour cells 3 5 and in recent years there has been much interest in the use of optical tools for cancer diagnostics because of their ability to detect biochemical changes occurring at the early stages of tumorigenesis 6 . Aside from being one of the most invasive and deadly human malignancies, GBM is a example model of a heterogeneous cancer 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%